Chapter Luoghi impliciti - Fancelli, Maria (Biblioteca di Studi di Filologia Moderna, 2021)
This short article aims to stimulate a rethinking of the deep cultural sedimentations that do not emerge on the surface of Claudio Magris' critical and narrative work. In this case we are dealing with books, writers, and locations in Tuscany which, on the basis of an initial exploration of the texts, constitute the underground and unspoken components of Claudio Magris' humanism.